A review of the parasites of deep-water fishes from Macaronesian Islands, North-East Atlantic Ocean - Costa, Graça (2018)
The deep-water fish fauna of Macaronesian islands is currently estimated at a total of 1029 different fish species, but records of both ecto- and endoparasites are from only about 30 of those species. This fact presents an exciting field of research for scientists interested in fish parasitology, by exploring the structure of parasite communities and their connections with ecological and oceanographic variables. Research on the effect of climatic changes on the parasite faunas, on the occurrence of fish parasites in man and its impact on human health, has not been carried out to date. The present review aims to collate our present knowledge about the parasites of deep-water fishes of Macaronesia, and to suggest directions for future research on the parasites of fishes from the deepwater realm. A checklist of the parasites infecting the deep-water fishes from this region is included.